Data Protection Impact Assessment Case Study for a Research Project Using Artificial Intelligence on Patient Data - Gültekin Várkonyi, Gizem; Gradišek, Anton (Informatica, 2020)
Advances in artificial intelligence, smart sensors, data mining, and other fields of ICT have resulted in a plethora of research projects aimed at harnessing these technologies, for example to generate new knowledge about diseases, to develop systems for better management of chronic diseases, and to assist the elderly with independent living. While the algorithms themselves can be developed using anonymized or synthetic data, conducting a pilot study is often one of the key components of a research project, and such studies unavoidably involve actual users with their personal data. Although one of the derogations stipulated in Article 89 of the GDPR is related to the data processed for scientific purposes, the GDPR still is applicable to that processing in a broader interpretation. The computer scientists and engineers working in research projects may not always be fully familiar with all the details of the GDPR, a close collaboration with a lawyer specialized in the European data protection legislation is highly beneficial for the success of a project. In this paper, we consider a hypothetical research project developed by an engineer dealing with sensitive personal data and a lawyer conducting Data Protection Impact Assessment to ensure legality and quality of the research project. Povzetek: Prispevek obravnava oceno učinka v zvezi z varstvom podatkov pri hipotetičnem raziskovalnem projektu, pri katerem se z metodami umetne inteligence analizira medicinske podatke uporabnikov.